Teachers' Efforts in Overcoming Calistung Learning Difficulties in Grade I Students - Rizky Iddha Purnaningtyas; Sukartono (Jurnal Elementaria Edukasia, 2024)
Difficulties that are often encountered when learning in lower grades are reading, writing and arithmetic which can be one of the factors inhibiting the learning process in class. The learning difficulties faced by students will greatly influence their academic results, because to achieve good academic results students also need to try hard in their studies. Reading and writing skills at elementary school level are very important in helping children understand how to convey the information they receive, while numeracy skills will support the development of children's logic and thinking abilities. The aim of this research is to describe the teacher's efforts in overcoming calistung learning difficulties in class I MI Muhammadiyah PK Wirogunan students. This research is a qualitative descriptive study using data collection techniques in the form of interviews, observation and documentation. The results of the research show that teachers overcoming calistung learning difficulties include: a) seek support and enthusiasm for intense learning; b) using the media book Islamic Children's Loves to Read (AISM); c) instructors (teachers) develop cooperation towards students. Supporting factors include: a) a comfortable learning environment; b) support from the school. While the inhibiting factors; a) lack of concentration of student learning; b) lack of support from parents. Solutions to overcome inhibiting factors include; the teacher gives assignments to students who experience learning difficulties; teachers try to help students who experience learning difficulties; teachers apply varied learning methods according to students' personalities.